Physiological functions and pharmacological and toxicological effects of p-octopamine - Stohs, Sidney J. (Drug and chemical toxicology (New York, N.Y. 1978), 2015)
Abstract p-Octopamine occurs naturally in plants, invertebrates and animals with diverse functions and effects. This review summarizes the chemistry, metabolism, receptor binding characteristics, known physiological functions, and pharmacological and toxicological effects of p-octopamine. Databases used included PubMed and Google Scholar Advanced. p-Octopamine binds to neuroreceptors in insects that are not present in humans, while exhibiting poor binding to α-1, α-2, β-1, and β-2 adrenergic receptors in mammalian systems. p-Octopamine modestly binds to β-3 adrenergic receptors and may therefore promote lipolysis and weight loss. p-Octopamine is produced in brain and nerve tissues of mammals and is present and can be measured in the blood of normal human subjects. p-Octopamine is considered to be a CNS stimulant in spite of the fact that it binds poorly to adrenergic receptors. Variations occur in blood levels in association with neurological and hepatic diseases. Its precise role in normal neurophysiology is unclear. No human studies have been reported that demonstrate adverse cardiovascular effects following oral administration. No human studies have examined the effects of p-octopamine on athletic performance or weight loss and weight management. A need exists for both animal and human safety and efficacy studies involving oral administration of p-octopamine.